Eight-year operation status and data analysis of the first human milk bank in East China - Hu Xiaoshan; Chu Xue; Zhang Jun; Liu Feng; Chen Xiaohui; Yu Zhangbin; Han Shuping (BMC, 2022)
Abstract Background Human milk banks (HMBs) are essential facilities for the selection, collection, testing, transportation,storage, and distribution of DHM for special medical needs. The aim of this analysis was to analyze the operation status and data over the last 8 years of operation of the first human milk bank (HMB) in East China. Methods Data related to the costs, donors, donation, pasteurization, and recipients were extracted from the web-based electronic monitoring system of the HMB for the period August 1, 2013 to July 31, 2021. Results Over the 8 years of operation, 1,555 qualified donors donated 7,396.5L of qualified milk at a cost of ¥1.94 million($306,051), with the average cost per liter of donor human milk being ¥262.3($41.4). The donors were between 25 and 30 years of age, and the majority (80.1%) were primipara. All the donated milk was pasteurized and subjected to bacteriological tests before and after pasteurization: 95.4% passed the pre-pasteurization tests, and 96.3% passed the post-pasteurization tests. A total of 9,207 newborns received 5,775.2L of pasteurized donor milk. The main reason for the prescription of donor human milk was preterm birth. As a result of continuous quality improvements, January 2016 witnessed a significant increase in the volume of qualified DHM and the number of qualified donors. However, in 2020, as a result of the restrictions related to the COVID-19 pandemic, the volume of qualified DHM and the number of qualified donors decreased. Conclusions Over its 8 years of operation, our HMB has made steady quality improvements in its screening and information processes. Continuous quality improvement is on ongoing need, along with recruiting more qualified donors and collecting donor human milk for vulnerable newborns.